RESPONSIBILITY FOR BUDGET OFFENSES - Blikhar, Mariia; Matviienko, Yaryna (Socio-economic relations in the digital society, 2023)
Budget Violations are a Significant Component of the Financial-Legal System in Ukraine, Regulating the Budgetary Process and Financial Relations among Its Participants. The article structures important aspects of budgetary violations, their legal responsibilities, and sanctions provided for by the relevant legislation. The Ukrainian system of responsibility in the field of budgetary legal relations encompasses a wide range of subjects and sanctions used to ensure compliance with financial norms and rules. This system is regulated by the current legislation, including the Budget Code of Ukraine, the Code of Ukraine on Administrative Offenses, and the Criminal Code of Ukraine. The definition of budget violations is a key aspect of analyzing this topic. A budget violation is the failure of a participant in the budget process to comply with the established procedure regulating the compilation, review, approval, amendment, and execution of the budget or the report on its execution. Participants in these violations include budget managers, recipients of budget funds, and local self-government bodies. Responsibility for such violations covers civil, disciplinary, administrative, and even criminal liability. For violations in the field of budgetary relations, the legislation provides a specific list of influence measures but also allows for the establishment of other sanctions through subordinate acts. Violations such as missing budget statements, improper budget fund allocation, and other forms of non-compliance can trigger the imposition of financial sanctions. An important characteristic is the specificity of budgetary relations, primarily having an imperative character and thereby constructing the structure of administrative responsibility in this area using formal elements of administrative-criminal acts. A comprehensive analysis and regulation of budget violations are essential elements of the stability and development of the state, ensuring compliance with financial norms and the accountability of budget process participants.